Effects of a PAF-antagonist (BN 52063) on bronchoconstriction and platelet activation during exercise induced asthma. - Wilkens, J H (1990)
1. The effects of a specific PAF acether antagonist (BN 52063) on the response to isocapnic hyperventilation with dry cold air (ISH study) and exercise (EIA study) were assessed in a single dose and short term treatment study in 10 patients with exercise induced asthma. 2. ISH challenge was performed twice within 1 h after administration of either placebo, 240 mg BN 52063 p.o. or inhalation of 2.4 mg BN 52063. Hyperventilation increased Raw from 0.30 +/- 0.02 to 0.89 kPa s l-1 (P less than 0.001) after the first challenge and from 0.28 +/- 0.04 to 0.84 +/- 0.06 kPa s l-1 (P less than 0.001) after the second challenge. Oral pretreatment with BN 52063 did not result in a reduction of bronchoconstriction during both challenges. A significant increase of Raw was noted immediately after inhalation of BN 52063. An inhibition of PAF induced platelet aggregation (by a factor of 2) occurred after oral administration of BN 52063 after both ISH challenges (P less than 0.05). No significant inhibition of PAF induced platelet aggregation was seen after inhalation of BN 52063. At concentrations up to 30 microM in vitro, BN 52063 inhibited PAF induced platelet aggregation in a dose dependent manner. The IC50 of BN 52063 against the aggregating effect of 1 microM PAF was 7.0 +/- 2.1 microM. 3. In the EIA study the patients were challenged on the third day of treatment with either placebo or 240 mg BN 52063 p.o. or 5 mg BN 52063 by inhalation. Peak expiratory flow rates (PEFR) fell by 155 +/- 37 1 min-1 after exercise.(ABSTRACT TRUNCATED AT 250 WORDS)